Motivasi, Pelatihan, Lingkungan Kerja dan Kompensasi Terhadap Kinerja Karyawan: Terapis Okupasional Klinik di Kota Surabaya - Istiatin; Sudarwati; Ulfah Diah Maryaningrum (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Motivation, training, work environment and compensation on employee performance (Occupational Therapists in Clinics in Surabaya City). This study aims to determine and explain the influence of motivation, training, work environment, and compensation on Occupational Therapists working in Clinics in Surabaya City. The population of all Occupational Therapists working in Clinics in Surabaya City is 40. Where the sampling technique uses the census method with a sample size of 40 respondents. Data collection using a questionnaire. The data analysis techniques used statistical analysis, namely multiple regression test, F test, t test, and coefficient of determination. The results of the study showed that 1) Motivation has a positive and significant effect on the performance of Occupational Therapists working in Clinics in Surabaya City. 2) Training has a positive and significant effect on the performance of Occupational Therapists working in Clinics in Surabaya City. 3) Work Environment has a positive and significant effect on the performance of Occupational Therapists working in Clinics in Surabaya City. 4) Compensation has a positive and significant effect on the performance of Occupational Therapists working in Clinics in Surabaya City. Which means that the higher the quality of motivation, training, work environment and compensation, the quality of employee performance will increase. Conversely, the lower the quality of motivation, training, work environment and compensation, it can cause a decrease in the quality of employee performance.